A Study of the Legal Control of Euthanasia in China - Yueqi, Zheng (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2023)
At one time, the Hippocratic Oath contained a prohibition of euthanasia, which was dictated by the social and human environment of the time. However, with the progress of society and the development of science and technology, euthanasia is not a new topic nowadays, and some countries in the world have legalized euthanasia. However, the issue of legal control of euthanasia is still relatively new in China, where it has not yet been legalised. One of the reasons why this issue has caused great controversy and discussion among all sectors of Chinese society is that euthanasia involves the advancement and development of multiple fields and disciplines such as medicine, law and ethics. One of the main questions is whether it is appropriate for China to legalise euthanasia, and if so, how it will be carried out. From a medical technical point of view, euthanasia already has mature and stable medical technology as a support, and its application is already operable; from a legal point of view, euthanasia has a corresponding legal theory and rights basis, and its legalisation has basically reached a consensus in the academic community; from an ethical and social cognition point of view, euthanasia does not violate traditional ethics and morality, and therefore is gradually being accepted and recognized by the public. After some research and analysis, this study concludes that euthanasia in China already has a theoretical and practical foundation, as well as the relevant scientific and technological conditions, and that giving euthanasia a legal status is of great significance to the social progress of China. The main reason for this is to solve the problems related to the legal control of euthanasia, that is, to legalize euthanasia, China need to consider how to build the legal control mechanism of euthanasia in the first place.